2021
DOI: 10.1519/jsc.0000000000004099
|View full text |Cite
|
Sign up to set email alerts
|

Acute Responses to Cycling Exercise With Blood Flow Restriction During Various Intensities

Abstract: Lauver, JD, Moran, A, Guilkey, JP, Johnson, KE, Zanchi, NE, and Rotarius, TR. Acute responses to cycling exercise with blood flow restriction during various intensities. J Strength Cond Res 36(12): 3366-3373, 2022-The purpose of this study was to investigate the acute physiological responses during cycling at various intensities with blood flow restriction (BFR). Subjects (N 5 9; V Ȯ2 peak 5 36.09 6 5.80 ml•kg 21 •min 21 ) performed 5 protocols: high-intensity (HIGH), control (CON-90), 90% of ventilatory thres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 39 publications
(86 reference statements)
1
5
0
Order By: Relevance
“…In contrast, the other studies analyzed exclusively men. In addition, the sample evaluated by Lauver et al [29] showed lower cardiorespiratory capacity (VO 2 peak) than the samples analyzed in the other studies (see ▶ Table 1). These results suggest that participant characteristics (e. g., training status), as well as characteristics of the interventions tested, may have impacted the response.…”
Section: Physiological Responsesmentioning
confidence: 70%
See 4 more Smart Citations
“…In contrast, the other studies analyzed exclusively men. In addition, the sample evaluated by Lauver et al [29] showed lower cardiorespiratory capacity (VO 2 peak) than the samples analyzed in the other studies (see ▶ Table 1). These results suggest that participant characteristics (e. g., training status), as well as characteristics of the interventions tested, may have impacted the response.…”
Section: Physiological Responsesmentioning
confidence: 70%
“…The sample size varied between 9 and 23 participants. Except for one study 29 , all studies relativized restriction pressure based on arterial occlusion pressure (AOP). Five studies tested more than one restriction pressure (%AOP).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations